The Transfer of Character Education Value in Children Literature: A Version of Indonesian and Translation Literature - Nur Azmi Alwi; Harris Effendi Thahar; Yasnur Asri; Atmazaki (International Conferences on Educational, Social Sciences and Technology)
This study aims at explaining the transfer of character education value in children literature in terms of Indonesian and translation version. This study was a qualitative research using descriptive method. The data in this study encompassed the value of character education which were explored from the narrator, characters’ utterance and characters’ act. There were two novels as the source of data, namely Laskar Pelangi as Indonesian literature and Nenek Hebat dari Saga as translation literature. The form of data inventory was used for collecting data. Three steps were employed to analyze data, which were: data reduction, data display and conclusion. The finding of study indicated that there was the transfer of character education value through children literature in terms of the behavior and attitude. These values closely related to (1) God, (2) self, (3) family, (4) society and nation, and (5) environment. In Laskar Pelangi’s novel, there were sub indicators especially in terms of Islam teaching, which are: discipline, creative, work-hard, honesty, tolerance and nationalism. In Nenek Hebat dari Saga’s novel, there were some sub indicators related to behavior such as Buddhism, wise, efficient, creative, and confident. This novel also described closely the habit, culture and nature of Japanese.